1996
DOI: 10.1074/jbc.271.51.32825
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Antigenic Determinants on the Extracellular Pyruvate Dehydrogenase Complex/Mimeotope Found in Primary Biliary Cirrhosis

Abstract: Affinity mass spectrometry (AMS) was used to evaluate the structural diversity of the E2 component of pyruvate dehydrogenase complex (PDC) in normal and diseased liver cells, including those from patients with the autoimmune disease primary biliary cirrhosis (PBC). Two different antibodies to PDC-E2, the immunodominant mitochondrial autoantigen in patients with PBC, were used. AMS was performed directly on frozen liver sections and purified bile duct epithelial cells. Mass spectrometric signals associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 36 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…The identity of the antigen at the apical surface has still not been established. 3,4,33 However, we have previously reported that the apical staining is also seen with mAbs against the branched chain ketoacid dehydrogenase complex-E2 and the 2-oxoglutarate dehydrogenase complex-E2 antigens. 6 These mAbs do not cross-react with PDC-E2.…”
Section: Discussionmentioning
confidence: 95%
“…The identity of the antigen at the apical surface has still not been established. 3,4,33 However, we have previously reported that the apical staining is also seen with mAbs against the branched chain ketoacid dehydrogenase complex-E2 and the 2-oxoglutarate dehydrogenase complex-E2 antigens. 6 These mAbs do not cross-react with PDC-E2.…”
Section: Discussionmentioning
confidence: 95%
“…Peptides released from immunoisolated complexes have been analyzed by both MALDI-TOF mass spectrometry and electrospray tandem mass spectrometry for epitope mapping (39,40), sequencing histocompatibility complex-binding peptides (41), and analysis of disease-related peptides (42). In addition to sequence-specific antibodies, pan-antibodies, such as anti-phosphotyrosine antibody, have also been used to isolate and to identify tyrosine-phosphorylated proteins on a global scale in response to extracellular stimulation (43,44).…”
Section: Resultsmentioning
confidence: 99%
“…A probable diagnosis requires the presence of two criteria, and a definite diagnosis requires all three [2] . The major mitochondrial autoantigens recognized by AMAs are members of the 2-oxoacid dehydrogenase complex (ODC) family [3][4][5] . Studies based on immunohistochemistry and affinity mass spectrometry have suggested that either PDC-E2 (a member of the ODC family) or a cross-reactive molecule is present in greatly increased amounts at the apical surface of biliary epithelial cells (BECs) from patients with AMA-positive or AMA-negative PBC, but not from normal individuals or patients with other liver diseases [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…The major mitochondrial autoantigens recognized by AMAs are members of the 2-oxoacid dehydrogenase complex (ODC) family [3][4][5] . Studies based on immunohistochemistry and affinity mass spectrometry have suggested that either PDC-E2 (a member of the ODC family) or a cross-reactive molecule is present in greatly increased amounts at the apical surface of biliary epithelial cells (BECs) from patients with AMA-positive or AMA-negative PBC, but not from normal individuals or patients with other liver diseases [4,5] . Additionally, in other studies, in addition to the intense staining of the apical surface of BECs, positive staining was observed in a subset of macrophages in portal lymph nodes [6] and in hepatocytes [7] .…”
Section: Introductionmentioning
confidence: 99%